Carbon-based nanocomposite lubricating film, preparation method and application thereof

CN118186340BActive Publication Date: 2026-10-20LANZHOU INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410300280.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-15
Publication Date
2026-10-20
Estimated Expiration
2044-03-15

AI Technical Summary

Technical Problem

本发明提供的碳基纳米复合润滑薄膜能够解决传统DLC碳基薄膜在摩擦过程中跑合期时间过长和摩擦系数过大的问题,纳米复合润滑薄膜的跑合期低于150次,可有效增加机械精密零部件活动摩擦副的可靠性

Benefits of technology

[0018]本发明通过纳米表面工程手段,在DLC表面进行降低跑合期功能层设计,设置了Ag层,Ag层为具有优异润滑作用的软质金属且其粘附性较好,可以在摩擦初期和对偶球接触面发生黏附,在摩擦时和DLC转移膜相互耦合,可以在对偶上快速形成具有纳米复合结构的稳定转移膜,从而降低DLC薄膜跑合期的摩擦系数和磨损率,进而得到低跑合期或者近零跑合期的固体润滑碳基薄膜材料,可有效降低精密部件摩擦副工作时的起始摩擦磨损,解决了传统DLC碳基薄膜在摩擦过程中跑合期时间过长和摩擦系数过大的问题。实施例的数据表明,本发明制得的碳基纳米复合润滑薄膜的跑合期低于150次,可有效增加机械精密零部件活动摩擦副的可靠性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118186340B_ABST
    Figure CN118186340B_ABST
Patent Text Reader

Abstract

The application provides a carbon-based nanocomposite lubricating film and a preparation method and application thereof, and belongs to the technical field of physical vapor deposition. The application provides a carbon-based nanocomposite lubricating film, which comprises a Cr transition layer, a DLC layer and an Ag layer which are sequentially stacked. The application designs a function layer for reducing a running-in period on the surface of the DLC through nanosurface engineering, and sets the Ag layer. The Ag layer is a soft metal with excellent lubricating effect and good adhesion, can adhere to the contact surface of the mating ball at the initial stage of friction, and can be coupled with the DLC transfer film during friction, so that a stable transfer film with a nanocomposite structure can be quickly formed on the mating pair, thereby reducing the friction coefficient and wear rate of the DLC film during the running-in period, and further obtaining a solid lubricating carbon-based film material with a low running-in period or a near-zero running-in period, which can effectively reduce the initial friction and wear of a precision component friction pair during work, and solves the problems of a long running-in period and a large friction coefficient of a traditional DLC carbon-based film during friction. The data of the examples show that the running-in period of the carbon-based nanocomposite lubricating film prepared by the application is less than 150 times, and the reliability of a mechanical precision component moving friction pair can be effectively increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of physical vapor deposition technology, and in particular to a carbon-based nanocomposite lubricating film, its preparation method, and its application. Background Technology

[0002] Friction consumes 30% of the world's primary energy and causes approximately 80% of machine parts to fail due to wear. Developed countries lose 5% to 7% of their GDP annually due to friction and wear. Particularly in high-precision mechanical parts, even minor friction and wear can have serious consequences. With increasingly stringent reliability requirements for high-end precision devices, higher demands are being placed on solid lubricants. For example, optoelectronic precision devices require solid lubricants with low or zero running-in periods. Diamond-like carbon (DLC) coatings possess excellent mechanical and tribological properties; however, DLC films have an excessively long running-in period (typically 2000–4000 cycles) during friction, and the high coefficient of friction and wear rate during this period significantly reduce the reliability of precision mechanical parts. Summary of the Invention

[0003] In view of this, the purpose of this invention is to provide a carbon-based nanocomposite lubricating film, its preparation method, and its application. The carbon-based nanocomposite lubricating film provided by this invention can solve the problems of excessively long running-in time and excessively high friction coefficient in traditional DLC carbon-based films during friction. The running-in time of the nanocomposite lubricating film is less than 150 cycles, which can effectively increase the reliability of moving friction pairs of precision mechanical parts.

[0004] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0005] The present invention provides a carbon-based nanocomposite lubricating film comprising a Cr transition layer, a DLC layer and an Ag layer stacked sequentially.

[0006] Preferably, the thickness of the Cr transition layer is 600–700 nm, the thickness of the DLC layer is 700–1700 nm, and the thickness of the Ag layer is 5–20 nm.

[0007] This invention also provides a method for preparing the carbon-based nanocomposite lubricating film described in the above technical solution, comprising the following steps:

[0008] The carbon-based nanocomposite lubricating film is obtained by magnetron sputtering on the substrate surface to sequentially form the Cr transition layer, DLC layer and Ag layer.

[0009] Preferably, the parameters for magnetron sputtering to form the Cr transition layer include: argon flow rate of 40 sccm, working pressure of 0.75 Pa, substrate bias of -100 V, Cr target purity of 99.95 wt%, target current of 4 A, and deposition time of 30–60 min.

[0010] Preferably, the magnetron sputtering parameters for forming the DLC layer include: an argon flow rate of 40 sccm, a methane flow rate of 0 sccm at 0 min, increasing the methane flow rate by 10 sccm every 5 min until the required methane flow rate is reached, followed by stabilizing the methane flow rate, wherein the required methane flow rate is 40–60 sccm, the working pressure is 0.75 Pa, the substrate bias voltage is -150–-250 V, the target material is a Cr target with a purity of 99.5 wt%, the target current is 2–4 A, the target voltage varies with the methane flow rate, and the deposition time is 120–240 min.

[0011] Preferably, the parameters for magnetron sputtering to form the Ag layer include: argon flow rate of 40 sccm, working pressure of 0.75 Pa, substrate bias of -50 to -100 V, target purity of 99.99 wt% Ag target, DC power of 30 to 100 W, and deposition time of 1 to 5 min.

[0012] Preferably, the substrate further includes pretreatment and argon ion glow discharge cleaning before magnetron sputtering. The pretreatment includes grinding, polishing, petroleum ether washing, anhydrous ethanol washing, petroleum ether washing, anhydrous ethanol washing, and nitrogen drying. The grinding uses 400#, 800#, 1400# and 2000# sandpaper in sequence, and the polishing uses W1.5 and W0.5 diamond polishing paste in sequence.

[0013] Preferably, the parameters for the argon ion glow discharge cleaning include: a bias voltage of -400 to -450V, an argon flow rate of 40 sccm, a working pressure of 1.65Pa, and a cleaning time of 20 to 25 minutes.

[0014] This invention also provides the application of the carbon-based nanocomposite lubricating film described above in the field of friction lubrication.

[0015] Preferably, the friction lubrication field includes optoelectronic precision devices.

[0016] The present invention provides a carbon-based nanocomposite lubricating film comprising a Cr transition layer, a DLC layer and an Ag layer stacked sequentially.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0018] This invention utilizes nanosurface engineering techniques to design a functional layer on the surface of DLC (Digital Ceramic Lithium-ion) film to reduce the running-in period. An Ag layer, a soft metal with excellent lubrication properties and good adhesion, is incorporated, allowing it to adhere to the contact surface of the mating spheres during the initial stage of friction. During friction, it couples with the DLC transfer film, rapidly forming a stable transfer film with a nanocomposite structure on the mating surface. This reduces the friction coefficient and wear rate during the DLC film's running-in period, resulting in a solid lubricating carbon-based thin film material with a low or near-zero running-in period. This effectively reduces the initial friction and wear of precision component friction pairs, solving the problems of excessively long running-in times and high friction coefficients in traditional DLC carbon-based thin films. Data from the embodiments show that the carbon-based nanocomposite lubricating film prepared by this invention has a running-in period of less than 150 cycles, effectively increasing the reliability of moving friction pairs in precision mechanical parts.

[0019] The present invention also provides a method for preparing the carbon-based nanocomposite lubricating film described in the above technical solution. The preparation method of the present invention is simple and easy to promote and apply. Attached Figure Description

[0020] Figure 1 This is a flowchart illustrating the preparation of a carbon-based nanocomposite lubricating film according to the present invention;

[0021] Figure 2 This is a schematic diagram of the structure of the carbon-based nanocomposite lubricating film provided by the present invention;

[0022] Figure 3 These are TEM comparison images of the carbon-based nanocomposite lubricating film and the Ag film without a top layer prepared in Example 1 of this invention.

[0023] Figure 4 This is a friction curve diagram of the carbon-based nanocomposite lubricating film and the pure DLC film prepared in Example 1 of the present invention under a 5N load.

[0024] Figure 5 This is a friction curve of the carbon-based nanocomposite lubricating film and the pure DLC film prepared in Example 2 of the present invention under a 10N load.

[0025] Figure 6 The images show the morphology of the wear scars on the paired ball and the TEM structure of the carbon-based nanocomposite lubricating film with ultra-low running-in period after friction with a pure DLC film prepared in Example 1 of this invention. Detailed Implementation

[0026] The present invention provides a carbon-based nanocomposite lubricating film comprising a Cr transition layer, a DLC layer and an Ag layer stacked sequentially.

[0027] Figure 2 This is a schematic diagram of the structure of the carbon-based nanocomposite lubricating film provided by the present invention.

[0028] In this invention, the thickness of the Cr transition layer is preferably 600-700 nm, the thickness of the DLC layer is preferably 700-1700 nm, more preferably 1527-1627 nm, and the thickness of the Ag layer is preferably 5-20 nm, more preferably 7-15 nm.

[0029] In this invention, when a friction experiment is conducted using a load of 2 to 15 N, the carbon-based nanocomposite lubricating film can reduce the running-in period and the coefficient of friction during friction.

[0030] This invention also provides a method for preparing the carbon-based nanocomposite lubricating film described in the above technical solution, comprising the following steps:

[0031] The carbon-based nanocomposite lubricating film is obtained by magnetron sputtering (MS) on the substrate surface to sequentially form the Cr transition layer, DLC layer and Ag layer.

[0032] In this invention, the substrate is preferably a metal substrate.

[0033] In this invention, the substrate preferably further includes pretreatment and argon ion glow discharge cleaning before magnetron sputtering. The pretreatment includes grinding, polishing, petroleum ether washing, anhydrous ethanol washing, petroleum ether washing, anhydrous ethanol washing, and nitrogen drying. The grinding uses 400#, 800#, 1400# and 2000# sandpaper in sequence, and the polishing uses W1.5 and W0.5 diamond polishing paste in sequence.

[0034] In this invention, the grinding and polishing are used to make the surface of the substrate mirror-like.

[0035] In this invention, the washing times for petroleum ether, anhydrous ethanol, petroleum ether, and anhydrous ethanol are preferably 15 to 20 minutes each.

[0036] In this invention, the preferred parameters for the argon ion glow discharge cleaning include: a bias voltage of -400 to -450V, an argon flow rate of 40 sccm, a working pressure of 1.65 Pa, and a cleaning time of 20 to 25 min in an argon atmosphere.

[0037] In this invention, the targets used in the magnetron sputtering include Cr targets and Ag targets. Preferably, the Cr and Ag targets are pre-sputtered before use; the purpose of pre-sputtering is to change the target surface from a poisoned state to a clean state.

[0038] In this invention, the pre-sputtering parameters preferably include: an argon flow rate of 40 sccm, a working pressure of 0.75 Pa, a medium-frequency power supply for the Cr target, a DC power supply for the Ag target, a current of 2-4 A for the medium-frequency power supply, a power of 50-150 W for the DC power supply, a pre-sputtering time of 30-60 min for the Cr target, and a pre-sputtering time of 10-15 min for the Ag target.

[0039] Before forming the Cr transition layer by magnetron sputtering, it is preferable to pre-sputter the target material. The purpose of the pre-sputtering target is to remove contaminants and oxides from the target surface. The parameters of the pre-sputtering target preferably include: a medium-frequency power supply with a current of 4A for the Cr target, a DC power supply with a power of 30-100W for the Ag target, and a pre-sputtering time of 5-10 minutes.

[0040] In this invention, the preferred parameters for magnetron sputtering to form the Cr transition layer include: argon flow rate of 40 sccm, working pressure of 0.75 Pa, substrate bias of -100 V, Cr target with a purity of 99.95 wt%, target current of 4 A, and deposition time of 30–60 min.

[0041] In this invention, the Cr transition layer has a nanocrystalline structure, and the particle size of the nanocrystalline structure is preferably 20-50 nm.

[0042] In this invention, the preferred parameters for magnetron sputtering to form the DLC layer include: an argon flow rate of 40 sccm, a methane flow rate of 0 sccm at 0 min, increasing the methane flow rate by 10 sccm every 5 min until the desired methane flow rate is reached, followed by stabilizing the methane flow rate, wherein the desired methane flow rate is 40–60 sccm, the working pressure is 0.75 Pa, the substrate bias is -150–-250 V, the target material is a Cr target with a purity of 99.5 wt%, the target current is 2–4 A, the target voltage varies with the methane flow rate (the target voltage gradually increases from 420 V to 550 V as the methane flow rate increases), and the deposition time is 120–240 min.

[0043] In this invention, the preferred parameters for magnetron sputtering to form the Ag layer include: argon flow rate of 40 sccm, working pressure of 0.75 Pa, substrate bias of -50 to -100 V, target purity of 99.99 wt% Ag target, DC power of 30 to 100 W, and deposition time of 1 to 5 min.

[0044] After forming the Ag layer, the present invention preferably further includes furnace cooling to obtain the carbon-based nanocomposite lubricating film.

[0045] Figure 1 This is a flowchart illustrating the preparation of a carbon-based nanocomposite lubricating film according to the present invention.

[0046] This invention also provides the application of the carbon-based nanocomposite lubricating film described above in the field of friction lubrication.

[0047] In this invention, the field of friction lubrication preferably includes optoelectronic precision devices.

[0048] The present invention does not impose any special limitation on the specific method of application, and any method known to those skilled in the art can be used.

[0049] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0050] Example 1

[0051] The preparation of a carbon-based nanocomposite lubricating film with ultra-low running-in period includes the following steps:

[0052] Step 1: Pre-treat the substrate surface by sanding it with 400#, 800#, 1400#, and 2000# sandpaper respectively, followed by polishing with W1.5 and W0.5 diamond polishing paste to achieve a mirror finish. Clean the polished substrate in the following order: petroleum ether → anhydrous ethanol → petroleum ether → anhydrous ethanol, each cleaning lasting 20 minutes, followed by drying with argon gas.

[0053] Step 2: Pre-sputtering of Cr and Ag targets. Argon flow rate is 40 sccm, working pressure is maintained at 0.75 Pa. The power supply used for Cr target is a medium frequency power supply with a current of 4 A, and the pre-sputtering time for Cr target is 40 min. The power supply used for Ag target is 100 W, and the pre-sputtering time is 10 min.

[0054] Step 3: Perform argon-ion glow discharge cleaning and target pre-sputtering on the substrate surface. Place the substrate in a vacuum chamber for argon-ion glow discharge cleaning. Adjust the pressure of the argon gas cylinder to 0.25 MPa and introduce argon gas at a flow rate of 40 sccm. Apply a bias voltage of -400V to the substrate, and maintain the pressure in the chamber at 1.65 Pa for 20 minutes. Then perform target pre-sputtering. For the Cr target, use a medium-frequency power supply with a current of 4A, a voltage of 448V, and a duty cycle of 60.2%. For the Ag target, use a DC power supply with a power of 100W, and the pre-sputtering time is 10 minutes.

[0055] Step 4: A Cr transition layer was prepared on the substrate surface using magnetron sputtering (MS) deposition with a Cr target and argon gas introduced. For the preparation of the Cr transition layer, the argon flow rate was 40 sccm, the working pressure was maintained at 0.75 Pa, the substrate bias voltage was -100 V, the target purity was 99.95 wt% Cr, a medium-frequency power supply was used, the target current was 4 A, and the deposition time was 30 min.

[0056] Step 5: Using magnetron sputtering (MS) deposition technology with a Cr target, and with argon and methane gases introduced, a DLC film was prepared on the Cr transition layer. The argon flow rate was 40 sccm. From 0 to 25 min, the methane gas flow rate was increased by 10 sccm every 5 min, sequentially increasing from 0 sccm to 50 sccm, and then stabilized at 50 sccm. The working pressure was maintained at 0.75 Pa, the substrate bias was -250 V, the target was a 99.95 wt% Cr target, and the target current was 3.5 A. The target voltage varied with the methane gas flow rate, gradually increasing from 420 V to 550 V with increasing methane flow rate. Once the methane gas flow rate stabilized, the target also stabilized. The deposition time was 180 min, and the DLC layer thickness was 1527 nm.

[0057] Step 6: Using magnetron sputtering (MS) deposition technology with an Ag target and argon gas introduced, an Ag thin film was prepared on the DLC layer. The argon gas flow rate was 40 sccm, the Ag target power was 50 W, the deposition time was 6 min, and the Ag layer thickness was 5 nm.

[0058] Friction and wear test: The experiment was conducted using a CSM standard friction testing machine. A 6mm diameter GCr15 metal ball was selected as the sliding friction pair. The sliding frequency was 3Hz, the friction amplitude was 5mm, and the cycle count was 2000 cycles under a 5N load. When the grinding ball was rubbed against pure DLC, the running-in period was 1100 cycles longer than that of a film with Ag deposits on the DLC surface, and the running-in period of DLC with a top Ag deposit was 120 cycles. The results are as follows. Figure 4 As shown.

[0059] Comparative Example 1

[0060] Same as Example 1, except that no Ag layer is formed.

[0061] Figure 3 The images show a TEM comparison of the carbon-based nanocomposite lubricating film and the Ag film without a top layer obtained in Example 1 of this invention. It can be seen that a 5nm Ag film is deposited on the top layer of the carbon-based nanocomposite lubricating film.

[0062] Figure 6The images show the morphology of the wear scars on the paired balls and the TEM structure of the carbon-based nanocomposite lubricating film after friction with a pure DLC film obtained in Example 1 of this invention, as well as the carbon film transfer film with an ultra-low running-in period. It can be seen that the carbon-based nanocomposite lubricating film formed an obvious transfer film on the paired balls after friction, while the pure DLC film did not form one after friction under the same conditions. Furthermore, the TEM of the transfer film shows that its microstructure is a composite structure of crystalline nano Ag clusters and amorphous carbon-based film.

[0063] Example 2

[0064] The preparation steps of a carbon-based nanocomposite lubricating film with ultra-low running-in period are as follows:

[0065] Step 1: Pre-treat the substrate surface by sanding it with 400#, 800#, 1400#, and 2000# sandpaper respectively, followed by polishing with W1.5 and W0.5 diamond polishing paste to achieve a mirror finish. Clean the polished substrate in the following order: petroleum ether → anhydrous ethanol → petroleum ether → anhydrous ethanol, each cleaning lasting 20 minutes, followed by drying with argon gas.

[0066] Step 2: Pre-sputtering of Cr and Ag targets. Argon flow rate is 40 sccm, working pressure is maintained at 0.75 Pa. The power supply used for Cr target is a medium frequency power supply with a current of 4 A, and the pre-sputtering time for Cr target is 40 min. The power supply used for Ag target is 120 W, and the pre-sputtering time is 10 min.

[0067] Step 3: Perform argon-ion glow discharge cleaning and target pre-sputtering on the substrate surface. Place the substrate in a vacuum chamber for argon-ion glow discharge cleaning. Adjust the pressure of the argon gas cylinder to 0.25 MPa and introduce argon gas at a flow rate of 40 sccm. Apply a bias voltage of -400V to the substrate, and maintain the pressure in the chamber at 1.65 Pa for 20 minutes. Then perform target pre-sputtering. For the Cr target, use a medium-frequency power supply with a current of 4A, a voltage of 448V, and a duty cycle of 60.2%. For the Ag target, use a DC power supply with a power of 100W, and the pre-sputtering time is 10 minutes.

[0068] Step 4: A Cr transition layer was prepared on the substrate surface using magnetron sputtering (MS) deposition with a Cr target and argon gas introduced. For the preparation of the Cr transition layer, the argon flow rate was 40 sccm, the working pressure was maintained at 0.75 Pa, the substrate bias voltage was -100 V, the target purity was 99.95 wt% Cr, the power supply used was a medium-frequency power supply with a target current of 4 A, and the deposition time was 30 min.

[0069] Step 5: Using magnetron sputtering (MS) deposition technology with a Cr target, and with argon and methane gases introduced, a DLC film was prepared on the Cr transition layer. The argon flow rate was 40 sccm. From 0 to 30 min, the methane gas flow rate was increased by 10 sccm every 5 min, sequentially increasing from 0 sccm to 60 sccm, and then stabilized at 60 sccm. The working pressure was maintained at 0.75 Pa, the substrate bias was -150 V, the target was a 99.5 wt% Cr target, and the target current was 4 A. The current through the target varied with the methane gas flow rate, and the target voltage gradually increased from 420 V to 550 V with increasing methane flow rate. Once the methane gas flow rate stabilized, the target state also stabilized. The deposition time was 150 min, and the DLC layer thickness was 1627 nm.

[0070] Step 6: Using magnetron sputtering (MS) deposition technology with an Ag target and argon gas introduced, an Ag thin film was prepared on the DLC layer. The argon gas flow rate was 40 sccm, the Ag target power was 60 W, the deposition time was 8 min, and the Ag layer thickness was 15 nm.

[0071] Friction and wear test: The experiment was conducted using a CSM standard friction tester. A 6mm diameter GCr15 metal ball was selected as the sliding friction pair. The sliding frequency was 6Hz, the friction amplitude was 5mm, and the cycle count was 4000 times under a 10N load. When the grinding ball was rubbed against pure DLC, the running-in period was 900 cycles longer than that of a film with Ag deposits on the DLC surface, and the running-in period of DLC with a top Ag deposit was 100 cycles. The results are as follows. Figure 5 As shown.

[0072] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A carbon-based nanocomposite lubricating film, characterized in that, It includes a Cr transition layer, a DLC layer and an Ag layer stacked sequentially; the thickness of the Cr transition layer is 600~700nm, the thickness of the DLC layer is 1627nm, and the thickness of the Ag layer is 15nm.

2. The method for preparing the carbon-based nanocomposite lubricating film according to claim 1, characterized in that, Includes the following steps: The carbon-based nanocomposite lubricating film is obtained by magnetron sputtering on the substrate surface to sequentially form the Cr transition layer, DLC layer and Ag layer.

3. The preparation method according to claim 2, characterized in that, The parameters for magnetron sputtering to form the Cr transition layer include: argon flow rate of 40 sccm, working pressure of 0.75 Pa, substrate bias of -100 V, target purity of 99.95 wt% Cr target, target current of 4 A, and deposition time of 30-60 min.

4. The preparation method according to claim 2, characterized in that, The parameters for magnetron sputtering to form the DLC layer include: argon gas flow rate of 40 sccm, methane gas flow rate of 0 sccm at 0 min, increasing the methane gas flow rate by 10 sccm every 5 min until the required methane gas flow rate is reached, and then stabilizing the methane gas flow rate (40-60 sccm), working pressure of 0.75 Pa, substrate bias of -150 to -250 V, target material of 99.5 wt% Cr target, target current of 2-4 A, target voltage varying with methane gas flow rate, and deposition time of 120-240 min.

5. The preparation method according to claim 2, characterized in that, The parameters for magnetron sputtering to form the Ag layer include: argon flow rate of 40 sccm, working pressure of 0.75 Pa, substrate bias of -50 to -100 V, target purity of 99.99 wt% Ag target, DC power of 30 to 100 W, and deposition time of 1 to 5 min.

6. The preparation method according to claim 2, characterized in that, Before magnetron sputtering, the substrate undergoes a pretreatment and argon ion glow discharge cleaning. The pretreatment includes grinding, polishing, petroleum ether washing, anhydrous ethanol washing, petroleum ether washing, anhydrous ethanol washing, and nitrogen drying. The grinding uses 400#, 800#, 1400#, and 2000# sandpaper in sequence, and the polishing uses W1.5 and W0.5 diamond polishing paste in sequence.

7. The preparation method according to claim 6, characterized in that, The parameters for the argon ion glow discharge cleaning include: bias voltage of -400~-450V, argon flow rate of 40sccm, working pressure of 1.65Pa, and cleaning time of 20~25min.

8. The application of the carbon-based nanocomposite lubricating film according to claim 1 in the field of friction lubrication.

9. The application according to claim 8, characterized in that, The field of friction and lubrication includes optoelectronic precision devices.

Citation Information

Patent Citations

  • Plastic bottle cover mould having surface with diamond like composite coating

    CN107587115A

  • Retainer for roller bearing

    JP2005147306A